Energy Assessment of Thermal Water Utilization in Swimming Pools - Predajnianska Anna; Takács Ján (Selected Scientific Papers: Journal of Civil Engineering, 2024)
In Slovakia, thermal water is used to the greatest extent in recreational facilities, which includes thermal swimming pools, medical sanatoriums or balneological facilities. Generally recreational facilities are the largest producers of waste pool water, which is discharged through a cooling pond or cooling canal most often into rivers. Wastewater temperature discharged from the recreational facility can be a maximum of 26 °C according to requirements of laws and regulations. The rate of energy use is closely related to the temperature thermal and wastewater which enter the swimming pool. The article is aimed at analysis of the energy balance and management of thermal water in the proposed swimming pool. Conclusion will be focused on increasing the rate of use of thermal water, where the pros and cons will be summarized.